Hukum Negara Tentang Perlindungan Tanah Dalam Persfektif Musyawarah Pastoral Ke Enam Di Dekenat Paniai - Titus Pekei (JURNAL PASTORAL KATEKETIK, 2024)
Article 33 of the Constitution of the Republic of Indonesia 1945 (UUD NRI 1945) is the magic of agrarian, mining, foreign investment, forestry, spatial planning and other related regulations. The state of Papuan customary land has no space and place in Indonesian law, mass distribution of land certificates is not a solution but the latest and centralized problem that can sertainya. The discussion material “state law on land protection” was a concern, but participants in the mee pastoral meeting did not receive an explanation of customary land, land titles and state land from the relevant bodies in Meuwodide. The muspas theme Aniya Yimu Beu Makida Koda Yoko Mei, meaning Back to my Holy Land...!? Communal customary land ownership is sacred but state law regulates it to be state land, privately titled land. Things are different and sometimes problems arise since Indonesian law does not see communal customary land, heirloom land according to clan, fam, clan. The nation-state must understand Papuan customary land without understanding state land and certificates but understanding the state of human participation of customary landowners in God's saving work.